Influence of Leadership Style and Organizational Commitment to Employee Work Performance in Regional Companies in Indonesia - Wiara Sanchia Grafita Ryana Devi; Yulianah Yulianah; Iskandar Ahmaddien (Budapest International Research and Critics University, 2022)
This research was conducted to find out the influence of leadership style on work performance, to find out the influence of organizational commitment to work achievement, and to find out the influence of leadership and organizational commitment to regional company work performance in Indonesia. This research is associative research with a quantitative approach. Data analysis techniques use multiple linear regression. The data used is primary, which is data obtained directly from the research object through the dissemination of questionnaires to 77 respondents. The results showed that leadership style had a positive and significant effect on work performance. Organizational commitment has a positive and significant effect on work performance. Leadership style and organizational commitment have a positive and significant effect on work performance.